SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

From “arrow storks” to search engine data: Google Trends reveals seasonality in search interest for migratory white storks (Ciconia ciconia) in Germany - Martin Kaatz; Michael Kaatz; Anne Meinzenbach; Steffen Springer; Michael Zieger (Zoologischer Anzeiger, 2023)

The Role of Space-Based Observations for Groundwater Resource Monitoring over Africa - Anne Springer; Teodolina Lopez; Michael Owor; Frédéric Frappart; Thomas Stieglitz (Surveys in Geophysics, 2023)
Africa is particularly vulnerable to climate change impacts, which threatens food security, ecosystem protection and restoration initiatives, and fresh water resources availability and quality. Groundwater largely contributes to the mitigation of climate change effects by offering short- to long-term transient water storage. However, groundwater storage remains extremely difficult to monitor. In this paper, we review the strengths and weaknesses of satellite remote sensing techniques for addressing groundwater quantity issues with a focus on GRACE space gravimetry, as well as concepts to combine satellite observations with numerical models and ground observations. One particular focus is the quantification of changes in groundwater resources in the different climatic regions of Africa and the discussion of possible climatic and anthropogenic drivers. We include a thorough literature review on studies that use satellite observations for groundwater research in Africa. Finally, we identify gaps in research and possible future directions for employing satellite remote sensing to groundwater monitoring and management on the African continent. Article Highlights Overview on the distribution and characteristics of African groundwater resources including future projections Combination of satellite and in situ observations with numerical models allows us to obtain a synoptic view of groundwater-related processes Summary of current concepts and achievements of satellite remote sensing-based groundwater monitoring and decision making over Africa

Evidence of daily hydrological loading in GPS time series over Europe - Anne Springer; Makan A. Karegar; Jürgen Kusche; Jessica Keune; Wolfgang Kurtz; Stefan Kollet (Journal of Geodesy, 2019)

Monthly and sub-monthly hydrological variability: in-orbit validation by GRACE level 1B observations - Annette Eicker; Anne Springer (Journal of Geodesy, 2016)